Research of the layout optimization in robotic mobile fulfillment systems. (23rd December 2020) - Wu, Shasha; Chi, Cheng; Wang, Wei; Wu, Yaohua
To improve the order fulfillment throughput and space utilization in the robotic mobile fulfillment system (RMFS), the research developed two design aspects: the layout design and the warehouse structural parameter configuration. Based on the semiopen queue network theory, we built the queue network model to estimate the performance of RMFS. A scheme was proposed to move the picking stations inside the storage area, and seven layout scenes were designed according to the location arrangement of stations and storage area. The performance estimation and parameter configuration platform were developed to support the experiments on layout optimization and parameter configuration. The result shows that the station's internal layout improves throughput when compared with the external scheme and increases space utilization without storage zones. Vertical zoning increases performance significantly. The performance is sensitive to the zoning strategy and storage area structural parameters.